The Poly I:C maternal immune stimulation model shows unique patterns of brain metabolism, morphometry, and plasticity in female rats - Casquero-Veiga, Marta; Lamanna-Rama, Nicolás; Romero-Miguel, Diego; Rojas-Marquez, Henar; Alcaide, Julia; Beltran, Marc; Nacher, Juan; Desco, Manuel; Soto-Montenegro, Maria Luisa (Frontiers in Behavioral Neuroscience, 2023)
Introduction: Prenatal infections are associated with an increased risk of onset of schizophrenia. Rodent models of maternal immune stimulation (MIS) have been extensively used in preclinical studies. However, many of these studies only include males, omitting pathophysiological features unique to females. The aim of this study is to characterize the MIS model in female rats using positron emission tomography (PET), structural magnetic resonance imaging (MR) and neuroplasticiy studies. Methods: In gestational day 15, Poly I:C (or Saline) was injected to pregnant Wistar rats to induce the MIS model. Imaging studies: [18F]-ﬂuoro-2-deoxy-D-glucose-PET scans of female-offspring were acquired at post-natal day (PND) 35 and PND100. Furthermore, T2-MR brain images were acquired in adulthood. Differences in FDG uptake and morphometry between groups were assessed with SPM12 and Regions of Interest (ROI) analyses. Ex vivo study: The density of parvalbumin expressin interneurons (PV), perineuronal nets (PNN) and parvalbumin expressing interneurons surrounded by perineuronal nets (PV-PNN) were evaluated in the prelimbic cortex and basolateral amygdala using confocal microscopy. ROIs and neuroplasticity data were analyzed by 2-sample T-test and 2 way-ANOVA analyses, respectively. Results: A significant increase in brain metabolism was found in all animals at adulthood compared to adolescence. MIS hardly modified brain glucose metabolism in females, highlighting a significant hypometabolism in the thalamus at adulthood. In addition, MIS induced gray matter (GM) enlargements in pituitary, hippocampus, substantia nigra and cingulate cortex, and GM shrinkages in some thalamic nuclei, cerebelar areas and brainstem. Moreover, MIS induced white matter shrinkages in the cerebellum, brainstem and corpus callosum, along with cerebrospinal fluid enlargements in the lateral and 4th ventricles. Finally, MIS reduced the density of PV, PNN and PV-PNN in the basolateral amygdala. Conclusion: Our work showed in vivo the differential pattern of functional and morphometric affectation in the MIS model in females, as well as the deficits caused at the synaptic level according to sex. The differences obtained highlight the relevance of including both sexes in psychiatric research in order to consider their pathophysiological particularities and successfully extend the benefits obtained to the entire patient population.